Predictors of early post-operative hypocalcemia after total parathyroidectomy in renal failure patients with secondary hyperparathyroidism - Guan, Tan Poh (2017)
Background: Secondary Hyperparathyroidism (SHPT) in renal failure patients are common and had different clinical presentations. Total parathyroidectomy is the surgery of choice in this group of patient. Hypocalceamia or even hungry bone syndrome are well known and is one of the serious complication in post-parathyroidectomy patient. The objectives of this study are to identify the predictors of early post-operative hypocalcaemia after total parathyroidectomy as well as the clinical presentations of secondary hyperparathyroidism in renal failure patient. Methods: Renal failure patient with secondary hyperparathyroidism who had underwent total parathyroidectomy in between 1st January 2007 till 31st December 2014 were retrospectively reviewed. The patients were divided into 2 groups according to their serum calcium level within 24 hours post surgery: the Hypocalcaemia group (25 patients) with post-operative serum calcium level of 2mmol/L or less, and the normocalcaemia group (43 patients), with the post-operative serum calcium level more then 2mmol/L. Patient details (age, gender and duration of renal failure) and preoperative blood investigations (preoperative serum calcium level , phosphorus level, alkaline phosphatase level ,serum albumin, serum intact parathyroid hormone and creatinine level) were analyzed in order to identify the predictor for early post-operative hypocalcaemia. The clinical presentations of secondary hyperparathyroidism in renal failure patient have also recorded.Results: By using multiple logistic regression analysis, alkaline phosphatase (ALP) has predictive value for early post operative hypocalcaemia with adjusted Odd ratio 1.004. Most of the patient who underwent surgery is symptomatic pre-operatively and the common presentations were bone pain (73%) and muscle weakness (21%). Hypocalcaemia is common in renal hyperparathyrosim patient post total parathyroidectomy. Up to 37% of our patient suffered from this post op complication. Conclusion: In conclusion, preoperative serum alkaline phosphatase correlate positively with the development of early post-operative hypocalcaemia so patient with high preoperative alkaline phosphatase should be monitored more closely in the early post operative period.